Environmental Sustainability Issues and Challenges in India - Sharma, H.S. (National Geographical Journal of India, 2022)
The last four or five decades saw a growing concern for the widening gap between human greed and nature's capacity to reproduce itself to satisfy this greed. Voices have been raised all over the world about global warming and climate changes, land degradation, depletion of ground water resources, biodiversity and pollution of air, water and land. Coming down to the regional and national levels the situation has become highly alarming. It has been noted that 20% of the world population uses 70% of the earth resources, while 20% lives on meager 5% resources. It appears that a symbiotic relationship between man and nature is gone and a new consumerist culture has taken deep routes. Sustainable development is perhaps the most quoted word in the few decades especially after publication of "Our Common Future" - A Report on the World Commission on Environment and Development by Brundtland in 1987. Sustainable development is a dynamic process and not static. It has been observed that during last 100 years the monsoon rainfall has been trendless particularly on all India scales but the trends in regional monsoonal rainfall during 100 year period have been observed. Trend analysis of 1 day extreme rainfall series based on the period 1951-2007 shows that extreme rainfall amounts are increasing in many places all over India. In Rajasthan deserts some pockets show an increasing trend of extreme rainfall events such as Luni Basin in July, 1979, Jaipur in July 1981 and Barmer in August 2006. The impacts of climate change are visible in all walks of life in India i.e. on agriculture, water resources, bio-diversity, coastal ecosystems, melting of Himalayan glaciers and human health. The paper deals with above issues highlighting the issues of climate change, sustainability and desertification with reference to India and Rajasthan